Clinic and genetic similarity assessments of atypical carcinoid, neuroendocrine neoplasm with atypical carcinoid morphology and elevated mitotic count and large cell neuroendocrine carcinoma - Ying Zhang; Weiya Wang; Qianrong Hu; Zuoyu Liang; Ping Zhou; Yuan Tang; Lili Jiang (BMC Cancer, 2022)
Abstract Background Pulmonary neuroendocrine neoplasms can be divided into typical carcinoid, atypical carcinoid, large cell neuroendocrine carcinoma, and small cell (lung) carcinoma. According to the World Health Organization, these four neoplasms have different characteristics and morphological traits, mitotic counts, and necrotic status. Importantly, “a grey-zone” neoplasm with an atypical carcinoid-like morphology, where the mitotic rate exceeds the criterion of 10 mitoses per 2 mm2, have still not been well classified. In clinical practice, the most controversial area is the limit of 11 mitoses to distinguish between atypical carcinoids and large cell neuroendocrine carcinomas. Methods Basic and clinical information was obtained from patient medical records. A series of grey-zone patients (n = 8) were selected for exploring their clinicopathological features. In addition, patients with atypical carcinoids (n = 9) and classical large cell neuroendocrine carcinomas (n = 14) were also included to compare their similarity to these neoplasms with respect to tumour morphology and immunohistochemical staining. Results We found that these grey-zone tumour sizes varied and affected mainly middle-aged and older men who smoked. Furthermore, similar gene mutations were found in the grey-zone neoplasms and large cell neuroendocrine carcinomas, for the mutated genes of these two are mainly involved in PI3K-Akt signal pathways and Pathways in cancer, including a biallelic alteration of TP53/RB1 and KEAP1. Conclusions Our findings indicate that neuroendocrine neoplasm with atypical carcinoid morphology and elevated mitotic counts is more similar to large cell neuroendocrine carcinoma than atypical carcinoid. Furthermore, this study may help improve diagnosing these special cases in clinical practice to avoid misdiagnosis.